2022
DOI: 10.1038/s41746-022-00645-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial enhancing viral hepatitis testing in primary care via digital crowdsourced intervention

Abstract: Despite the availability of hepatitis B virus (HBV) and hepatitis C virus (HCV) testing in primary care, testing rates in China remain low. Social media is an inexpensive means of disseminating information and could facilitate hepatitis testing promotion. We evaluated the capacity of digitally crowdsourced materials to promote HBV/HCV testing uptake via a randomized controlled trial (identifier: ChiCTR1900025771), which enrolled 750 Chinese primary care patients. We randomized patients (1:1) to receive crowdso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our study participants had a good baseline awareness regarding hepatitis B and C screening (56.7%) which improved after the intervention (77.3%). Though there is paucity of research evaluating the impact of video education on Hepatitis screening; however two recent studies showed similar results [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study participants had a good baseline awareness regarding hepatitis B and C screening (56.7%) which improved after the intervention (77.3%). Though there is paucity of research evaluating the impact of video education on Hepatitis screening; however two recent studies showed similar results [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%